A Path to More Meaningful Technical Services Assessment. Issue 1 (2nd January 2021) - Corrado, Edward M.; Jaffe, Rachel
ABSTRACT: In recent years, there have been many initiatives aiming to improve library assessment by making better use of operational data.  While most LIS administrators and stakeholders believe assessment is important, too often many of the quantitative measures traditionally used may satisfy demands from above, come up short in terms of oﬀering direction for meaningful or positive change.This may be especially true when it comes to technical services departments. This article will discuss the need for meaningful assessment in order to support decision-making in technical services, investigate the traditional data collected, and suggest an approach utilizing information from performance appraisals that could lead to a more holistic assessment of library departments.